2023
DOI: 10.1021/acsengineeringau.3c00031
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonization of Agriculture: The Greenhouse Gas Impacts and Economics of Existing and Emerging Climate-Smart Practices

Kamila Kazimierczuk,
Sarah E. Barrows,
Mariefel V. Olarte
et al.

Abstract: The worldwide emphasis on reducing greenhouse gas (GHG) emissions has increased focus on the potential to mitigate emissions through climate-smart agricultural practices, including regenerative, digital, and controlled environment farming systems. The effectiveness of these solutions largely depends on their ability to address environmental concerns, generate economic returns, and meet supply chain needs. In this Review, we summarize the state of knowledge on the GHG impacts and profitability of these three ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 142 publications
(324 reference statements)
0
2
0
Order By: Relevance
“…However, there are concerns about increased land use, decreased productivity, and hurdles to implementation in some situations . Indeed, the potential benefits of regenerative agriculture depend on the precise agroecosystem where it is applied. , In some situations, there may be benefits, but in others, there may not. Consequently, it is important to adopt the most suitable agricultural practice for a particular agroecosystem, which often requires initial field trials that compare different approaches.…”
Section: Increasing Crop Yields Resilience and Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are concerns about increased land use, decreased productivity, and hurdles to implementation in some situations . Indeed, the potential benefits of regenerative agriculture depend on the precise agroecosystem where it is applied. , In some situations, there may be benefits, but in others, there may not. Consequently, it is important to adopt the most suitable agricultural practice for a particular agroecosystem, which often requires initial field trials that compare different approaches.…”
Section: Increasing Crop Yields Resilience and Nutritionmentioning
confidence: 99%
“…Consequently, it is important to adopt the most suitable agricultural practice for a particular agroecosystem, which often requires initial field trials that compare different approaches. In addition, there are still many uncertainties about the relative benefits and limitations of different approaches under different conditions, and so more research is required . Syngenta, an agrochemical company, has reported that changing from conventional to regenerative agricultural practices could sequester around a billion tons of carbon dioxide globally per year, which could draw down more than 10% of anthropogenic carbon emissions into the soil over 25 years .…”
Section: Increasing Crop Yields Resilience and Nutritionmentioning
confidence: 99%